ANALISIS SWOT DALAM PELAKSANAAN PEMBELAJARAN SISTEM DUA SESI PADA KONDISI KETERBATASAN SARANA DAN PRASARANA DI SD NEGERI 10 PEGUYANGAN - Chindytia; Gede Agung, Anak Agung; Evi Puspita, Ni Putu; Manuangga Pradnyana, Ida Bagus; Wulandari Putri, Ni Putu Ayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the two-session learning system and analyze the strengths, weaknesses, opportunities, and threats in its implementation at SD Negeri 10 Peguyangan. This study employed a qualitative approach with a descriptive research design. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted by identifying internal and external school factors using SWOT analysis within the context of School-Based Management (SBM). The results showed that the implementation of the two-session learning system at SD Negeri 10 Peguyangan was motivated by limited classroom availability and school facilities. In terms of strengths, the school has competent teachers, structured school management, diverse school programs, and strong cooperation among school members. In terms of weaknesses, the study found limited classroom facilities, reduced effective learning time, less optimal student conditions during afternoon sessions, and shortages of teaching staff in certain subjects. Opportunities include government support, classroom construction assistance programs, advances in educational technology, and the potential involvement of parents and school committees. Meanwhile, threats include the potential decline in learning effectiveness, teacher fatigue, impacts on the school’s image, and limited parental support. Based on the SWOT analysis, adaptive school development strategies are needed by optimizing internal strengths and utilizing external opportunities to improve learning quality.